Akurasi dan Akuntabilitas Penilaian Kinerja Guru Pendidikan Agama Islam - Lubna Lubna (Universitas Islam Negeri Mataram, 2014)
There are a great number of teachers of Islamic religious education who hold a professional diploma and yet have not realized the tasks of competent professional teacher. The four indicators of competent and professional teacher, as these are elaborated in Statutes and Regulations, have not been integrated in teacher performance. This problem must be resolved. It requires a system that can control the implementation of the principles of professional teacher while at the same time does not ruin teacher’s profession and capability. This article offers professional-based assessment and evaluation of teacher performance as a medium for a regular control. This system will be able to measure teacher performance referring to their skills and to avoid deviation in the evaluation between what is taught and the subject being taught concerning teachers’ professional skills. With this professional-based evaluation system, the processes of evaluation and assessment become objective, accurate and accountable.